Economic optimal dispatch of active distribution network with CCHP multi-microgrid based on analytical target cascading - Yang, Yongbiao; Ai, Dengxin; Zhang, Li; Zheng, Yawen (Frontiers in Energy Research, 2024)
When multiple CCHP microgrids are integrated into an active distribution network (ADN), the microgrids and the distribution network serve as distinct stakeholders, making the economic optimal dispatch of the system more complex. This paper proposes a distributed dispatch model of ADN with CCHP multi-microgrid, and refines the objective functions of each region. The analytical target cascading approach (ATC) is employed to model the power transaction as virtual sources/loads, and solve the optimal dispatch in parallel. Case studies demonstrate the proposed distributed model is capable of achieving economic optimization for both stakeholders.